Endoscopic Colorectal Stenting: Lessons Learned from a Two-Decade Journey - Oner, Muharrem; Abbas, Maher A. (Clinics in Colon and Rectal Surgery, 2023)
Endoscopic colorectal stenting has gained momentum over the last two decades as a viable alternative to surgical intervention in a subgroup of patients with colorectal disease. Stenting can be used as a temporizing bridge to surgical intervention or as a definitive treatment measure. Patient selection and the technical expertise of the endoscopist are of paramount importance to optimize the clinical outcome. Technical skills in therapeutic endoscopy and the choice of proper equipment including the consumables are required for the conduct of a safe and successful procedure. In this article, we share the lessons learned from a two-decade journey of the senior author with therapeutic endoscopy.
Keywords: colorectal stricture; colon obstruction; endoscopic stent; technical tips